Comparison of trapping profiles between d-peptides and glutathione in the identification of reactive metabolites. (2015) - Laine, Jaana E.; Häkkinen, Merja R.; Auriola, Seppo; Juvonen, Risto O.; Pasanen, Markku
Abstract: Qualitative trapping profile of reactive metabolites arising from six structurally different compounds was tested with three differentd -peptide isomers (Peptide 1, gly–tyr–pro–cys–pro–his-pro; Peptide 2, gly–tyr–pro–ala–pro–his–pro; Peptide 3, gly–tyr–arg–pro–cys–pro–his–lys–pro) and glutathione (GSH) using mouse and human liver microsomes as the biocatalyst. The test compounds were classified either as clinically "safe" (amlodipine, caffeine, ibuprofen), or clinically as "risky" (clozapine, nimesulide, ticlopidine; i.e., associated with severe clinical toxicity outcomes). Our working hypothesis was as follows: could the use of short different amino acid sequence containingd -peptides in adduct detection confer any add-on value to that obtained with GSH? All "risky" agents' resulted in the formation of several GSH adducts in the incubation mixture and with at least one peptide adduct with both microsomal preparations. Amlodipine did not form any adducts with any of the trapping agents. No GSH and peptide 2 and 3 adducts were found with caffeine, but with peptide 1 one adduct with human liver microsomes was detected. Ibuprofen produced one Peptide 1-adduct with human and mouse liver microsomes but not with GSH. In conclusion, GSH still remains the gold trapping standard for reactive metabolites. However, targetedd -peptides could provide additional information about protein binding potential of electrophilic agents, but their clinical significance needs to be clarified using a wider spectrum of chemicals together with other safety estimates.